2015
DOI: 10.1051/0004-6361/201425518
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Titan’s atmospheric photochemistry

Abstract: We studied the photochemistry of frozen ice of a polar Titan's atmospheric molecule cyanodiacetylene (HC 5 N) to determine the possible contribution of this compound to the lower altitude photochemistry of haze layers found on Titan. We used infrared analysis to examine the residue produced by irradiation of solid HC 5 N at λ > 300 nm. The resulting polymer is orange-brown in color. Based on theoretical analysis and the general tendency of HC 5 N and C 4 N 2 to undergo similar ice photochemistry at longer wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 57 publications
(69 reference statements)
1
8
0
Order By: Relevance
“…Thus, the model suggests the presence of complex hydrocarbon compounds and precursors of haze particles at low altitudes. This result is also consistent with several laboratory studies showing a complexification of hydrogenated molecules from small hydrocarbons to more complex by UV irradiations (Yoon et al, 2014;Couturier-Tamburelli et al, 2015Carrasco et al, 2018).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the model suggests the presence of complex hydrocarbon compounds and precursors of haze particles at low altitudes. This result is also consistent with several laboratory studies showing a complexification of hydrogenated molecules from small hydrocarbons to more complex by UV irradiations (Yoon et al, 2014;Couturier-Tamburelli et al, 2015Carrasco et al, 2018).…”
Section: Resultssupporting
confidence: 93%
“…Their conclusion is that photoabsorption by haze particles in this FUV domain would trigger a rich solid-state chemistry at low altitudes. In a similar way photolysis of HC 5 N led to residues containing aromatic signatures around 3.3 µm and C -H stretching around 3.4 µm (Couturier-Tamburelli et al, 2015). The authors concluded that this photolysis drives the formation of more and more complex polymers which are precursors of haze particles.…”
Section: Discussionmentioning
confidence: 89%
“…Figure 6 compares the subtraction infrared spectrum at 70 K of the benzene ice (case 1) after-before UV photolysis with the infrared spectrum of amorphous benzene ice (50 K). The peaks marked with asterisks, on the left side of the figure, correspond to amorphous benzene features while the ones, marked with triangles, on the right side, are characteristic of the formation of polymeric material, as has already been highlighted by Couturier-Tamburelli et al (2015, 2018, in the case of HC 5 N or HC 3 N photolysis.…”
Section: Simulation Of Benzene Photochemical Aging At Its Condensatiomentioning
confidence: 69%
“…Because solar photons at longer-wavelengths reach lower altitudes, condensed molecules could undergo further processes driven by those long wavelength photons (λ > 300 nm), particularly at and below the lower stratosphere (<150 km) where temperatures also drop below 150 K, all the way to the surface of Titan (Lavvas et al, 2008). Interaction of these photons with the aerosols and ices could lead to two different processes: (a) photodesorption of the volatile condensate molecules through direct or indirect mechanisms (Thrower et al, 2008), (b) longwavelength photons could induce solid-state photochemistry leading to the formation of covalent bonds and new condensed volatiles organic compounds (Anderson et al, 2016) as well as solid organics like aerosols as demonstrated recently in laboratory experiments (Couturier-Tamburelli et al, 2014;Couturier-Tamburelli et al, 2015;Gudipati et al, 2013). One or several layers of ices could cover Titan's aerosols in the atmosphere or at the surface (Anderson et al, 2016;Raulin and Owen, 2002).…”
Section: Introductionmentioning
confidence: 91%